Ответы и объяснения

2013-10-21T15:24:11+04:00
А) ( x+39)-43=27              ( x+39)-43=27
   x-39-43=27                   
 x-39-43=27  
   x=27+39+43                  x-82=27
   x=109                           x=27+82
                                        x=109

б)(60-x)-16=20                          (60-x)-16=20
60+x-16=20                              60+x-16=20
x=20-60+16                              44+x=20
x=-24                                      x=20-44
                                               x=-24